2017
DOI: 10.1002/dmrr.2917
|View full text |Cite
|
Sign up to set email alerts
|

Progression of skin autofluorescence of AGEs over 4 years in patients with type 1 diabetes

Abstract: The skin autofluorescence of advanced glycation end-products progresses in patients with type 1 diabetes, more if they have diabetic nephropathy, less if they are treated by continuous subcutaneous insulin infusion. This progression is associated with the development of nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“… 44 In persons with type 1 diabetes, we have reported that the progression of SAF was more pronounced if diabetic nephropathy was present, and less pronounced under treatment with continuous subcutaneous insulin infusion, which suggests that reducing glucose variability may help. 45 Nephroprotection can be another track, if the high autofluorescence in CKD predicts cancer, which remains to be determined. We have reported that SAF quickly increases during an acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
“… 44 In persons with type 1 diabetes, we have reported that the progression of SAF was more pronounced if diabetic nephropathy was present, and less pronounced under treatment with continuous subcutaneous insulin infusion, which suggests that reducing glucose variability may help. 45 Nephroprotection can be another track, if the high autofluorescence in CKD predicts cancer, which remains to be determined. We have reported that SAF quickly increases during an acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between sAF and the history of diabetic foot ulcers seems of especial interest, as the diabetic foot syndrome both relies on micro (neuropathy) and macroangiopathy (peripheral arterial disease). The pioneer work from Meerwaldt already mentioned a relation between sAF and diabetic neuropathy [ 25 ], which was later confirmed in T1D [ 26 ]. SAF is high in subjects with peripheral arterial disease [ 27 ], and predicts rates of amputations [ 28 ] and mortality [ 29 ].…”
Section: Discussionmentioning
confidence: 98%
“…Below we highlight findings from two main topics: hyperglycemia and inflammation. Some studies focused on hyperglycemia's role as a major determinant for DSPN in T1DM [32], by demonstrating that prolonged hyperglycemia may lead to nerve damage by raising reactive oxygen species (ROS) concentration and oxidative stress [33,34], and enhancing the production of advanced glycation end products [35,36]. Other studies focused on the role of chronic inflammation leading to DSPN [37], some of them underlining the importance of activation of the TNF-alpha system [24,38] and the enhanced expression of pro-inflammatory cells, possibly influenced by persistent poor glycemic control [39].…”
Section: Epidemiologymentioning
confidence: 99%